Implementation of early warning score (EWS) simulation on nurses’ competence: A scoping review - Lia Puji Astuti; Afridawaty MJ (Holistik Jurnal Kesehatan, 2026)
Background: The implementation of an early warning system (EWS) is a systematic strategy for early detection of acute deterioration in patients through structured monitoring of physiological parameters. However, various studies have shown that EWS implementation in inpatient settings remains suboptimal, primarily due to nurses' limited knowledge, confidence, and clinical skills in interpreting and responding to the resulting scores. Simulation-based education is considered an effective approach to improving clinical competence because it allows for active, reflective, and applied learning in a safe environment. Purpose: To analyze the effectiveness of the EWS simulation method in improving nurse competence through a scoping review approach. Method: This study adopted a scoping review approach based on the Joanna Briggs Institute (JBI) guidelines, with reporting structured according to the PRISMA framework. A systematic search of the literature was carried out across PubMed, ProQuest, ScienceDirect, Scopus, SAGE, and EBSCO to identify English-language publications from 2014 to 2024. The search strategy was developed using the PICOS framework, incorporating a range of keywords related to nursing, simulation, and early warning system (EWS). Results: The findings demonstrate that simulation-based EWS training, including high-fidelity and web-based approaches, consistently improves nurses’ knowledge, clinical skills, confidence, and attitudes in recognizing and responding to patient deterioration. This effectiveness is attributed to the ability of simulation to provide realistic, practice-based learning experiences. Most studies reported significant enhancement in early detection and clinical decision-making abilities following simulation interventions. Conclusion: Simulation-based EWS training is an effective strategy for strengthening nurses’ competence in detecting and managing acute patient deterioration. Integrating simulation into continuous nursing education is recommended to enhance clinical performance, support patient safety, and improve the overall quality of care. Suggestion: Future research can use a more robust experimental design and involve various clinical settings to evaluate the effectiveness of simulation more comprehensively, especially in the aspects of team communication and clinical response to patient deterioration.   Keywords: Acute Deterioration; Early Warning System; Nurses’ Competency; Simulation.